Policy on Synthetic Biology: Deliberation, Probability, and the Precautionary Paradox - Wareham, Christopher (Bioethics, 2015)
Synthetic biology is a cutting-edge area of research that holds the promise of unprecedented health benefits. However, in tandem with these large prospective benefits, synthetic biology projects entail a risk of catastrophic consequences whose severity may exceed that of most ordinary human undertakings. This is due to the peculiar nature of synthetic biology as a ‘threshold technology’ which opens doors to opportunities and applications that are essentially unpredictable. Fears about these potentially unstoppable consequences have led to declarations from civil society groups calling for the use of a precautionary principle to regulate the field. Moreover, the principle is prevalent in law and international agreements. Despite widespread political recognition of a need for caution, the precautionary principle has been extensively criticized as a guide for regulatory policy. We examine a central objection to the principle: that its application entails crippling inaction and incoherence, since whatever action one takes there is always a chance that some highly improbable cataclysm will occur. In response to this difficulty, which we call the ‘precautionary paradox,’ we outline a deliberative means for arriving at threshold of probability below which potential dangers can be disregarded. In addition, we describe a Bayesian mechanism with which to assign probabilities to harmful outcomes. We argue that these steps resolve the paradox. The rehabilitated PP can thus provide a viable policy option to confront the uncharted waters of synthetic biology research.